Combined Spinal-Epidural Analgesia for Laboring Parturient with Arnold-Chiari Type I Malformation: A Case Report and a Review of the Literature - Clark K. Choi; Kalpana Tyagaraj (Case Reports in Anesthesiology)
Anesthetic management of laboring parturients with Arnold-Chiari type I malformation poses a difficult challenge for the anesthesiologist. The increase in intracranial pressure during uterine contractions, coughing, valsalva maneuvers, and expulsion of the fetus can be detrimental to the mother during the process of labor and delivery. No concrete evidence has implicated high cerebral spinal fluid pressure on maternal and fetal complications. The literature on the use of neuraxial techniques for managing parturients with Arnold-Chiari is extremely scarce. While most anesthesiologists advocate epidural analgesia for management of labor pain and spinal anesthesia for cesarean section, we are the first to report the use of combined spinal-epidural analgesia for managing labor pain in a pregnant woman with Arnold-Chiari type I malformation. Also, we have reviewed the literature and presented information from case reports and case series to support the safe usage of neuraxial techniques in these patients.